Development and validation of inversion technique for substorm current wedge using ground magnetic field data. Issue 3 (26th March 2014) - Chu, Xiangning; Hsu, Tung‐Shin; McPherron, Robert L.; Angelopoulos, Vassilis; Pu, Zuyin; Weygand, James J.; Khurana, Krishan; Connors, Martin; Kissinger, Jennifer; Zhang, Hui; Amm, Olaf
Abstract The classic substorm current wedge model represents ground and space magnetic perturbations measured during substorms. We have developed an inversion technique to calculate parameters determining the intensity and geometry of the current system using magnetic field data at midlatitudes. The current wedge consists of four segments: a sheet‐like field‐aligned current downward to the ionosphere postmidnight, a westward current across the auroral bulge, an upward sheet‐like current from the westward surge premidnight, and an eastward current in the equatorial plane. The model has five parameters including the current strength, the locations, and breadths of the two field‐aligned current sheets. Simultaneous changes in the ring current are represented by the superposition of a symmetric ring current and a partial ring current characterized by three additional parameters. Parameters of the model are determined as a function of time based on midlatitude ground magnetometers, using realistic field lines and accounting for Earth's induction. The model is validated by a variety of techniques. First, the model predicts more than 80% of the variance in the observations. Second, the intensity of the current wedge and the ring current follows the same trends of the westward electrojet and the ring current indices. Third, the intensity of the westward electrojet agrees extremely well with the intensity of the current wedge. Finally, spacecraft observations of the aurora correspond with the evolution deduced from the model. This model of the substorm current wedge provides a valuable tool for the study of substorm development and its relation to phenomena in space.